New software product development: Bibliometric analysis - Mata, P. N.; Martins, J. M.; Ferreira, J. C. (Journal of the Knowledge Economy, 2025)
The aim of this article is to conduct a comprehensive bibliometric analysis of the existing literature in the domain of new software product development. The research methodology is based on bibliometrics, cluster analysis and meta-analysis of key indicators of knowledge dissemination and publications about the new software product in the Scopus scientometric database for 2003–2022.Through bibliometric analysis, this study provides valuable information on the trends, patterns and impact of research and publications in the field of new software product development. Based on the literature reviewed, known research areas, influential authors and new directions are identified, thus providing a comprehensive overview of the current state of knowledge in the field of new software product development. The number of publications dedicated to new software products has steadily increased over the past two decades, indicating a growing interest in this field among researchers and scholars. The United States, China, and Germany emerged as the leading countries in terms of the number of publications, highlighting their strong presence in software development and technological advancements. Meta-analysis demonstrates the significant impact of Engineering, Mathematics, and Social Sciences on the publication count of the new software product. Overall, the findings highlight the widespread interest and interdisciplinary nature of software product development, with particular emphasis on the role of Computer Science and Engineering in driving advancements in this domain. The conducted bibliometric analysis can serve as a basis for further research and help researchers and practitioners to identify knowledge gaps and directions for future research.